A permanência dos estudantes que ingressaram por ação afirmativa : a assistência estudantil em foco - Nunes, Roseli Souza dos Reis (2016)
With the implementation of affirmative action policies for the admission in higher education, reflecting the demands of organized social movements, the university area, which historically favored the entry of an elite that holds better socioeconomic conditions, became occupied by a larger number of students of popular origin. In this context, this research presents arguments that justified the changes in the form of admission in public universities and analyzes the remaining policies in public higher education with an emphasis on student assistance since 2003. The objective of this study is to analyze factors that affect the permanence of students who entered by affirmative action in the context of student assistance policies. This is a descriptive and exploratory study of qualitative approach that uses documentary sources and database information for analysis of the socioeconomic profile of campus undergraduate students who entered in 2013 and 2014 and requested student assistance or were awarded with it in the institution. They were tabulated the form responses of the online socioeconomic study, informed by the applicant for student assistance, and the scholarships record for those students. The qualitative research is conducted based on the analysis of interviews with 8 (eight) students benefit by some kind of student assistance or signed up and were not awarded by the program and 2 (two) program coordinators, as reference for this analysis the concept of cultural capital of Pierre Bourdieu. In the profile, it was observed that most student assistance requests was made by students of full-time, who attended high school in a public school, declared be black or brown skin color and are from courses with an academic bachelor's degree. Besides that, 62.33% of the beneficiaries by the student assistance are female and 37.67% are male, and 70.27% are in the age group 18-24 years old. It is consistent with Pierre Bourdieu when it is given to the family the responsibility of transmitting the cultural heritage, thus constituting the cultural capital. It is perceived that the low education of the parents, the family situation of socio-economic vulnerability and the low quality of public education at primary and secondary levels, committed the accumulation of cultural capital of the students. It was found that 57.57% of mothers and 72.68% of the fathers have not completed high school and only 8.6% of mothers and 3.94% fathers have a college degree. Among the elements that interfere with the permanence of the student in the early years of the undergraduate course, it became clear the choice of the course, the reception of the student, the university environment, the cultural capital, the student work and the student assistance. Furthermore, an analysis on the performance of the subjects of the first year of entry, understanding that this is an element that interferes with the permanence and its analysis, contributes to the management and monitoring of students in the course. In conclusion, the student assistance is a program with high visibility at the University and constitutes a fundamental support for the permanence of students with socioeconomic vulnerabilities. Those who fail the student assistance seek other forms of support, such as monitoring, scientific research, extension and other trainee grants. However, if they have not resources to fund the studies, they have a threatened permanence in the course.